AmAMP1 from Acropora millepora and damicornin define a family of coral-specific antimicrobial peptides related to the Shk toxins of sea anemones. (January 2021) - Mason, B.; Cooke, I.; Moya, A.; Augustin, R.; Lin, M.-F.; Satoh, N.; Bosch, T.C.G.; Bourne, D.G.; Hayward, D.C.; Andrade, N.; Forêt, S.; Ying, H.; et al.
Abstract: A candidate antimicrobial peptide (AmAMP1) was identified by searching the whole genome sequence of Acropora millepora for short (<125AA) cysteine-rich predicted proteins with an N-terminal signal peptide but lacking clear homologs in the SwissProt database. It resembled but was not closely related to damicornin, the only other known AMP from a coral, and was shown to be active against both Gram-negative and Gram-positive bacteria. These proteins define a family of AMPs present in corals and their close relatives, the Corallimorpharia, and are synthesised as preproproteins in which the C-terminal mature peptide contains a conserved arrangement of six cysteine residues. Consistent with the idea of a common origin for AMPs and toxins, this Cys motif is shared between the coral AMPs and the Shk neurotoxins of sea anemones. AmAMP1 is expressed at late stages of coral development, in ectodermal cells that resemble the "ganglion neurons" of Hydra, in which it has recently been demonstrated that a distinct AMP known as NDA-1 is expressed. Highlights: AmAMP1 from the coral Acropora is active against some Gram + ve and -ve bacteria including a coral pathogen. AmAMP1 is related to damicornin from Pocillopora ; these define a coral-specific peptide family. AmAMP1/damicornin homologs are structurally related to the Shk neurotoxins of sea anemones. AmAMP1  is expressed in ectodermal cells resembling neurons and the AMP1 protein is likely to be active in surface mucous.